Control of macrophage metabolism and activation by mTOR and Akt signaling. Issue 4 (August 2015) - Covarrubias, Anthony J.; Aksoylar, H. Ibrahim; Horng, Tiffany
Graphical abstract: Highlights: The diverse functions of macrophages in various physiological and pathophysiological contexts are likely to be supported by distinct metabolic programs. Macrophage polarizing signals induce metabolic shifts that accommodate acquisition and execution of effector activities. mTORC1 and Akt are major metabolic nodes that are targeted by macrophage polarizing signals to coordinate such metabolic shifts. Perturbations in mTORC1 and Akt signaling alter macrophage metabolism and activation. Modulation of macrophage metabolism can be explored in many disease contexts, including intracellular bacterial infection, sepsis, inflammatory bowel disease, and cancer. Abstract: Macrophages are pleiotropic cells that assume a variety of functions depending on their tissue of residence and tissue state. They maintain homeostasis as well as coordinate responses to stresses such as infection and metabolic challenge. The ability of macrophages to acquire diverse, context-dependent activities requires their activation (or polarization) to distinct functional states. While macrophage activation is well understood at the level of signal transduction and transcriptional regulation, the metabolic underpinnings are poorly understood. Importantly, emerging studies indicate that metabolic shifts play a pivotal role in control of macrophage activation and acquisition of context-dependent effector activities. The signals that drive macrophage activation impinge on metabolic pathways, allowing for coordinate control of macrophage activation and metabolism. Here we discuss how mTOR and Akt, major metabolic regulators and targets of such activation signals, control macrophage metabolism and activation. Dysregulated macrophage activities contribute to many diseases, including infectious, inflammatory, and metabolic diseases and cancer, thus a better understanding of metabolic control of macrophage activation could pave the way to the development of new therapeutic strategies.